1993
DOI: 10.1084/jem.178.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex class II-restricted presentation of an internally synthesized antigen displays cell-type variability and segregates from the exogenous class II and endogenous class I presentation pathways.

Abstract: Although reported examples of endogenous antigen (Ag) presentation by major histocompatibility complex (MHC) class II molecules have increased, the mechanisms governing this process remain poorly defined. In this communication, we describe an experimental system designed to examine the mechanisms governing class II presentation of internal Ag. Our target peptide is processed from a transmembrane protein constitutively expressed by a variety of nucleated cells (MHC class I, H-2Ld), is naturally displayed by MHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 62 publications
2
45
0
1
Order By: Relevance
“…For example, the UV inactivation of A/PR8/34 influenza virus (PR8) or treatment of infected antigen-presenting cells (APCs) with protein synthesis inhibitors prevents the presentation of the NA79 epitope (12). Similar observations have been made for an epitope derived from influenza matrix protein 1 (24) and an epitope derived from the MHC class I H2-L d molecule (39).…”
supporting
confidence: 51%
“…For example, the UV inactivation of A/PR8/34 influenza virus (PR8) or treatment of infected antigen-presenting cells (APCs) with protein synthesis inhibitors prevents the presentation of the NA79 epitope (12). Similar observations have been made for an epitope derived from influenza matrix protein 1 (24) and an epitope derived from the MHC class I H2-L d molecule (39).…”
supporting
confidence: 51%
“…54). Although some investigators have found that TAP is not required for presentation of endogenously synthesized MHC II-restricted peptides (41,55,56), others have found that presentation is TAP dependent (57,58). It has been suggested that this discrepancy in the apparent requirement for TAP is due to differences in Ag stability, because rapidly degraded, but not long-lived cytosolic Ag requires TAP for Ag presentation (59).…”
Section: Discussionmentioning
confidence: 99%
“…However, some endogenous Ags, those synthesized within the APC, can gain access to the MHC II presentation pathway (25). Indeed, it appears that some epitopes can be generated only through the processing of endogenous Ag (26,27). Recent studies have implicated both cytosolic proteases, including the proteasome, and endosome resident proteases in the generation of epitopes from endogenous proteins, including transmembrane proteins (28 -30).…”
Section: D4mentioning
confidence: 99%